Exploring the Impact of Attachment to School Counselors on Moral Emotion Development in Slow Learners: A Case Study in Central Java Inclusive Schools - Nugraini, Erna Dwi; Mulawarman, M; Sugiharto, DYP (Universitas Negeri Padang, 2023)
Emotion becomes an integral part that derives children's moral behavior. Moral emotion controls moral transgression by making children aware of the consequences of their actions. However, not all children can control their emotions, e.g., slow learners. The slow learners in this study are students in inclusive schools in Central Java. Their status as inclusive students resulted in feelings of alienation, even bullying. One factor affecting moral emotions is children's attachment to attachment figures, including school counselors. This study aims to determine the attachment pattern between slow learners and school counselors in developing moral emotions. This research used a qualitative method with a case study approach. Data was collected by interviews, direct observations, focused group discussions (FGD), and documentation. The results showed that the level of slow learners‘ attachment security was affected by school counselors‘ affection, responsiveness, sensitivity, and availability, both physically and emotionally. Higher security slow learners demonstrated higher trust and disclosure, and are emotionally attached to school counselors compared to those with lower security. On the other hand, attachment is associated with moral emotions of shame, guilt, and righteous anger but is not significantly associated with empathy. The findings are expected to increase awareness of school counselors in showing support and affection toward slow learners in inclusive schools, especially while providing services to fulfill guidance and counseling functions of understanding, development, and prevention.